Literature Review 2020-2025: Innovation of Pop-Up Book Employing Problem Based Learning to Improve Students’ Learning Outcomes and Critical Thinking Skills - Winda Kumalasari; Sri Haryani; Arif Widiyatmoko; Bambang Subali (FKIP - Universitas Riau, 2026)
The rapid development of digital learning media necessitates that educators implement engaging and effective instructional strategies. One innovative tool gaining significant attention is the pop-up book. This study aims to evaluate the enhancement of students’ learning outcomes and critical thinking skills through the integration of pop-up books within a Problem Based Learning (PBL) approach. The research methodology employed is a Systematic Literature Review (SLR) covering publications from 2020 to 2025. A total of 500 articles indexed in Google Scholar were analyzed using bibliometric mapping via Publish or Perish and VOSviewer, with twenty five key articles selected for in-depth examination. The findings indicate that contemporary research focuses heavily on the synergy between interactive learning media and instructional models, with the combination of pop-up books and PBL emerging as a frequently explored variable. Evidence suggests that employing pop-up books within a PBL framework effectively improves both academic performance and critical thinking abilities. Consequently, this integration serves as a practical and innovative teaching strategy to meet the demands of modern education.